Immune Modulation of Asian Folk Herbal Medicines and Related Chemical Components for Cancer Management - Patanapongpibul, Manee; Chen, Qiao-Hong (Current Medicinal Chemistry, 2019)
Various exciting immunotherapies aiming to address immune deficiency induced by tumor and treatment hold promise in improving the quality of life and survival rate of cancer patients. It is thus becoming an important and rewarding arena to develop some appropriate immune modulators for cancer prevention and/or treatment. Exploitation of natural products-based immune modulators is of particular imperative because the potential of numerous traditional herbal medicines and edible mushrooms in boosting human immune system has long been verified by folklore practices. This review summarizes the immune modulations of various herbal medicines and edible mushrooms, their crude extracts, and/or key chemical components that have been, at least partly, associated with their cancer management. This article also tabulates the origin of species, key chemical components, and clinical studies of these herbal medicines and edible mushrooms.
Keywords: tonic herbs